Gender Role in School Bullying - Neupane, D (Journal of Chitwan Medical College, 2014)
School bullying with reference to gender was performed in Kathmandu. The general aim of this research was to analyze the relationship between bullying and victimization with response to gender among Nepalese school adolescents. The study was correlational in design employing a pen-and-paper self-report survey. Within the survey, two separate instruments measured the criterion variables bullying and victimization. Participants were drawn from three private schools of Kathmandu. These schools were chosen in random selection. The number of participations was 104 school students. The study investigated the prevalence of bullying in the school with reference to gender. The result from the survey indicates that the boys are more bully than girls are. Boys have reported higher mean scores of physical bullying, verbal bullying, physical victimization and verbal victimization. On the other hand, girls have reported higher mean scores of indirect bullying and victimization. Gender differences in bullying and victimization were as expected and as social role theory and previous research would predict, with boys reporting higher direct and overall levels of bullying and victimization than girls. Similarly, and in accordance with the literature, girls reported higher levels of indirect bullying and victimization than boys are. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10847 Journal of Chitwan Medical College 2014; 4(1): 37-41